2008
DOI: 10.1162/jocn.2008.20049
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Frontal Lobe Plays a Critical Role in Facial Emotion Recognition

Abstract: The ventromedial prefrontal cortex has been implicated in a variety of emotion processes. However, findings regarding the role of this region specifically in emotion recognition have been mixed. We used a sensitive facial emotion recognition task to compare the emotion recognition performance of 7 subjects with lesions confined to ventromedial prefrontal regions, 8 subjects with lesions elsewhere in prefrontal cortex, and 16 healthy control subjects. We found that emotion recognition was impaired following ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
141
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 49 publications
14
141
1
1
Order By: Relevance
“…Finally, the modified valence hypothesis (Borod, 1993;Davidson, 1984) could explain the response bias obtained in this study by suggesting that a faint emotion can asymmetrically activate valence-specific prefrontal regions involved in an emotional experience (e.g. Heberlein et al 2008). This activation could then bias attention toward the side of space contralateral to the activated hemisphere, making a right-side choice more likely following LH activation, and a left-side choice more likely after RH activation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, the modified valence hypothesis (Borod, 1993;Davidson, 1984) could explain the response bias obtained in this study by suggesting that a faint emotion can asymmetrically activate valence-specific prefrontal regions involved in an emotional experience (e.g. Heberlein et al 2008). This activation could then bias attention toward the side of space contralateral to the activated hemisphere, making a right-side choice more likely following LH activation, and a left-side choice more likely after RH activation.…”
Section: Discussionmentioning
confidence: 64%
“…Wild et al 2001), or because subjective experiences of an emotion are generated in the prefrontal cortex during emotion perception (e.g. Heberlein, Padon, Gillihan, Farah & Fellows, 2008), then it could cause the response bias. For example, two faint positive faces might activate left frontal regions more than right frontal regions, because of the left frontal region's specialization in positive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the VMPFC has been implicated in nearly all aspects of emotional experience, expression, recognition, and regulation (e.g., Cooney, Joormann, Atlas, Eugene, & Gotlib, 2007;Drevets & Raichle, 1998;Heberlein, Padon, Gillihan, Farah, & Fellows, 2008;Lane, Reiman, Bradley, et al, 1997). Age-related changes in any of these aspects could contribute to the valence reversal within this region.…”
Section: Au a A Thor Notementioning
confidence: 96%
“…For example, OFC and ACC regions are thought to play a role in representing arousal, and this role has been invoked to explain medial PFC involvement in recognizing high-arousal emotions (Adolphs, 2002;Öngur & Price, 2000). Two recent studies have examined the effects of PFC damage on both emotional experience and recognition (Heberlein et al, 2008;Hornak et al, 2003), and both of these studies found a relationship between measures of specifically sad mood experience and sadness recognition. Heberlein et al (2008) found that in people with ventromedial frontal (but not other prefrontal) cortex damage, there was a relationship between ratings of sad faces and lab-induced sad emotion.…”
Section: Prefrontal Cortex In Face Emotionmentioning
confidence: 99%
“…Two recent studies have examined the effects of PFC damage on both emotional experience and recognition (Heberlein et al, 2008;Hornak et al, 2003), and both of these studies found a relationship between measures of specifically sad mood experience and sadness recognition. Heberlein et al (2008) found that in people with ventromedial frontal (but not other prefrontal) cortex damage, there was a relationship between ratings of sad faces and lab-induced sad emotion. They explained these findings by positing a model which bears some similarity to that proposed by Barrett et al (2007), discussed above, for the amygdala: People with damage to VMF cortices may be less sensitive to others' emotional expressions, including of distress, and therefore may show less sad mood in situations including laboratory mood inductions.…”
Section: Prefrontal Cortex In Face Emotionmentioning
confidence: 99%